Study Controlling Turnover Intention Among Early Childhood Education Teachers: The Role of Core Commitment Values and Compensation Satisfaction - Atika, Aisyah Nur; Yuliati, Nanik; Umami, Yuniarta Syarifatul; Supriadi, Bambang (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Teachers are a key factor in realizing educational quality, particularly in early childhood education (ECE), where professional commitment, innovation, and resilience are crucial. High turnover intention among ECE teachers threatens the continuity and quality of learning. This study aims to develop a model for implementing the basic values of commitment—comprising dedication to goals, efficiency, innovation, and teaching quality—moderated by compensation satisfaction, to reduce turnover intention. The research focuses on understanding how internal and external motivational factors contribute to teacher retention in ECE institutions. A quantitative approach was employed involving 119 ECE teachers in Jember Regency, East Java, Indonesia. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3.0). Variables measured include core values of organizational commitment, compensation satisfaction, and turnover intention control. Validity and reliability tests confirmed the robustness of the measurement model. The results show that all four dimensions of teacher commitment have a significant negative relationship with turnover intention. Teachers who demonstrate strong alignment with institutional goals, efficiently use resources, engage in innovation, and uphold high teaching standards are significantly less likely to express an intention to leave. Compensation satisfaction was found to be a significant moderating variable that strengthened the relationship between commitment and reduced turnover. Furthermore, a supportive work environment—characterized by physical and emotional well-being, positive peer relationships, and opportunities for professional development—was identified as a contextual enhancer of retention. Theoretically, this study contributes to the refinement of organizational commitment theory in the context of early childhood education in developing countries. Practically, the findings provide actionable insights for policymakers and school administrators to implement targeted retention strategies that address both intrinsic motivations and extrinsic conditions. Future studies are encouraged to include broader variables such as leadership, career advancement, and psychological well-being, as well as test the model across different educational settings.